Global Business Value Innovations Building Innovation Capabilities for Business Strategies (International Marketing and Management Research,, 2018)
This edited collection is a uniquely positioned contribution of interrelated research papers about global business value transformations in both offline and online (digital) worlds. With chapters spanning multiple business disciplines such as strategy, organizational behavior and e-commerce, this book explores the impact of cross-cultural issues, characteristics and challenges with regard to global value innovations. The authors analyze the effects of institutional and regulatory change on international marketing and management from both traditional and digital perspectives, providing concepts and cases for students and academics.